A method of optimizing aircraft autostabilizer systems - Wolkovitch, J. (College of Aeronautics, 1957)
A novel procedure for the optimization of aircraft autostabilizer systems is presented. The procedure is straightforward, and its application does not result in demands for autostabilizer systems of prohibitive complexity. Many important non-linear effects may be included with only slight extra complication in the required calculations. The procedure is applicable, in the first place, to piloted aircraft, - the essence of the procedure being the assumption that the purpose of thy: autostabilizer is to reduce the effort demanded of the pilot in executing a given manoeuvre or attaining a given response. Although the presence of the pilot is explicitly taken into account in the calculations no form of pilot's transfer function need be specified. It is shown how the procedure may be modified to form an approximate procedure for the optimization of autostabilizers for pilotless aircraft having linear autostabilizer characteristics and linear aircraft dynamics. The results of some calculations presented herein support a suggestion that this approximate optimization procedure may also be frequently applied with success to pilotless aircraft having certain non-linearities, either in the autostabilizer system or in the aircraft dynamics.